Presentation of Religious Tourism Pattern Based on Foundation Data Theory in International Borders - Ali Rostami; Mohammad Aidi; Alireaza slambolchi; Mohammadreza Rabiee Mandejin (تحقیقات کاربردی علوم جغرافیایی)
Tourism is now considered as one of the most important income industries of the world. Tourism as one of the main and basic approaches can be used in solving problems resulted from unemployment problems and downturn in different countries and the twenty-year vision of Iran specially consider tourism and attracting tourists. The huge volume of the tourists in the world are religious tourists and most of these religious tourists choose Mehran international border for entry and exit from Iran for doing pilgrimage and their religious affairs due to being safe and vicinity to The Holy of Holies in Iraq. This research aims at designing and explaining religious tourism model in Mehran International Border. Having determining the sample size qualitatively via snowball method, 14 experts of religious tourism including academics and trustees of religious tourism were recognized and they were interviewed directly and the research findings showed that religious tourism pattern in Mehran International Border has six main components including casual conditions (religious and tribal communities, provincial infrastructures, common border of Iraq and vicinity to The Holy of Holies, advertisements) categories (tourism and its subcategories, religious places in Iran and Iraq, security) grounds (commercial free zone in Mehran welfare and health services, economic part of religious tourism), interferer factors (political factors, conveying affairs to non-governmental sector, weather changes), strategies (cooperating with educational centers and universities, increasing governmental investing, using capacities of religious days) consequences & results (income and creating jobs, people’s persistence in border and non-immigration, cultural development of province, destruction of environmental, road and jungles of province) which could be introduced as a proper pattern for religious tourism in Mehran International Border according to the opinion of experts.